Discussion of the progress and completion of history, life after death, and the resurrection of human persons in Christianity and Islam - Hermanni, Friedrich 1958- (2002)
Pannenberg replied to a question about the apparent opposition of faith and reason in Christian theology: Our ability to understand has limits; that is the nature of human reason. If there is something beyond the limits of our understanding, that does not contradict reason. On the contrary, faith and reason complete one another, if the latter is correctly understood, not with the claim of being able to understand and evaluate everything, and if, at the same time, faith does not regard itself as omniscient. Our theological knowledge is “incomplete,” as Paul says, and therefore finite. The humility of faith itself brings us to this understanding of reason in the knowledge that completion is still in the future.